Portuguese emigration Factbook 2018 - Pires, Rui Pena (2019)
In 2017, Portuguese emigration continued its sustained downward trend, with around 85 thousand individuals leaving the country. Overall, the decrease is strongly correlated with the recovery of the Portuguese economy, especially in terms of job creation, as well as the reduction in attraction of destination countries such as the United Kingdom and Angola. The 2018 edition of the Factbook includes data updated to 2017 (or last year available) on total Portuguese emigration and to the main destination countries, as well as on emigrants' remittances.